THE ROLE OF DATA ANALYTICS MATURITY, ORGANIZATIONAL LEARNING, AND KNOWLEDGE-ORIENTED LEADERSHIP IN SUPPORTING ORGANIZATIONAL EXPLORATIVE AND EXPLOITATIVE INNOVATION CAPABILITY - Ratna A.K.K., Destina
Introduction: The ability to continuously innovate has been widely realized as crucial for organizations to survive and be sustainable. Hence, the activity of explorative and exploitative innovation becomes essential for organizations. One of the keys to successful innovation in a turbulent environment is leadership from top management and executives in organizations. Moreover, the role of knowledge-oriented leadership in promoting innovation within organizations has received considerable attention in recent studies. Besides knowledge-oriented leadership, organizational learning is also considered an important factor in boosting innovation capability in organizations. Purpose: Developing a data analytics maturity model and testing the influence of data analytics maturity, organizational learning, and knowledge-oriented leadership in increasing the company's explorative and exploitative innovation capabilities.